IP(3) 3-Kinase Opposes NGF Driven Neurite Outgrowth - Eva, Richard (Public Library of Science, 2012)
The inositol (1,4,5) trisphosphate 3-kinases comprise a family of enzymes (A, B, and C) that phosphorylate the calcium mobilising molecule inositol (1,4,5) trisphosphate (IP(3)) to generate inositol (1,3,4,5) tetrakisphosphate. This molecule can function as a second messenger, but its roles are not completely understood. The A isoform of inositol (1,4,5) trisphosphate 3-kinase localises to filamentous actin within dendritic spines in the hippocampus and is implicated in the regulation of spine morphology and long term potentiation, however the mechanisms through which it signals in neuronal cells are not completely understood. We have used NGF driven neurite outgrowth from PC12 cells as a platform to examine the impact of signaling via inositol (1,4,5) trisphosphate 3-kinase activity in a neuronal cell. We have found that the catalytic activity of the enzyme opposes neurite outgrowth, whilst pharmacological inhibition of inositol (1,4,5) trisphosphate 3-kinase leads to a significant increase in neurite outgrowth, and we show that the reduction in neurite outgrowth in response to inositol (1,4,5) trisphosphate 3-kinase activity correlates with reduced ERK activity as determined by western blotting using phosphorylation-specific antibodies. Our findings suggest a novel neuronal signaling pathway linking metabolism of IP(3) to signaling via ERK.